Human Capital, Social Mobility and the Skill Premium - Konstantinos Angelopoulos; Jim Malley; Apostolis Philippopoulos (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper develops a dynamic general equilibrium model to highlight the role of human capital accumulation of agents differentiated by skill type in the joint determination of social mobility and the skill premium. We first show that our model captures the empirical co-movement of the skill premium, the relative supply of skilled to unskilled workers and aggregate output in the U.S. data from 1970-2000. We next show that endogenous social mobility and human capital accumulation are key channels through which the effects of capital tax cuts and increases in public spending on both pre- and post-college education are transmitted. In particular, social mobility creates additional incentives for the agents which enhance the beneficial effects of policy reforms. Moreover, the dynamics of human capital accumulation imply that, post reform, the skill premium is higher in the short-to medium-run than in the long-run.
Keywords: E62; J31; J62; 330; social mobility; skill premium; tax and education policy